2021
DOI: 10.1002/cpe.6815
|View full text |Cite
|
Sign up to set email alerts
|

Towards a sustainable artificial intelligence: A case study of energy efficiency in decision tree algorithms

Abstract: Artificial intelligence has been showing accelerated growth due to its use in solving problems in several application domains. This success results from the convergence of large amounts of data, high‐performance computing, and precision of machine learning (ML) algorithms. Even with the relevance of ML algorithms, little is known about their computational requirements and power consumption, which has become an important task to achieve greener computing. This work aims to evaluate the energy efficiency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Software approach: Some software approaches for energy savings are the investigation of computational requirements and their influence on energy consumption with code optimizations, the influence of the number of instances and features in the overall energy consumption, 26 identifying which part of the algorithm is consuming most of the energy (hotspots), 27 hyperparameters choice and its impact on energy. 28 Regarding the library, Holt & Sievert 29 Another aspect related to the algorithms that have emerged as a promising design alternative to better performance and energy efficiency in ML is Approximate Computing (AC). Different techniques and designs have been proposed at both hardware and software levels.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Software approach: Some software approaches for energy savings are the investigation of computational requirements and their influence on energy consumption with code optimizations, the influence of the number of instances and features in the overall energy consumption, 26 identifying which part of the algorithm is consuming most of the energy (hotspots), 27 hyperparameters choice and its impact on energy. 28 Regarding the library, Holt & Sievert 29 Another aspect related to the algorithms that have emerged as a promising design alternative to better performance and energy efficiency in ML is Approximate Computing (AC). Different techniques and designs have been proposed at both hardware and software levels.…”
Section: Related Workmentioning
confidence: 99%
“…Software approach: Some software approaches for energy savings are the investigation of computational requirements and their influence on energy consumption with code optimizations, the influence of the number of instances and features in the overall energy consumption, 26 identifying which part of the algorithm is consuming most of the energy (hotspots), 27 hyperparameters choice and its impact on energy 28 …”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…The parameter values selected may influence not only the quality of results but also power consumption. Similarly, in [45], the authors proposed a methodology to estimate the energy consumption of Decision Tree-based ML algorithms and to identify the most energyconsuming parts and parameters. They monitored the energy consumption for each function or piece of code using RAPL and showed that they could reduce the energy consumption without reducing accuracy.…”
Section: E Software Optimization: Programming Languages Algorithms De...mentioning
confidence: 99%
“…Besides, the usage of a decision tree provides an opportunity to save time [11]. Literature analysis shows applications decision-tree (DT) based, decision support in the SD area [12]. The work aims to evaluate the energy efficiency of the Machine Learning algorithms to identify their energy hotspots.…”
Section: Introductionmentioning
confidence: 99%